Roles of organelle-specific autophagy in hepatocytes in the development and treatment of non-alcoholic fatty liver disease - Yizhi Zhang; Yu Chen; Lishao Guo (Chinese Medical Journal, 2022)
Abstract. Non-alcoholic fatty liver disease (NAFLD) is a disorder of lipid metabolism. The lipotoxic intermediates of lipid metabolism cause mitochondrial dysfunction and endoplasmic reticulum stress. Organelle-specific autophagy is responsible for the removal of dysfunctional organelles to maintain intracellular homeostasis. Lipophagy contributes to lipid turnover by degrading lipid droplets. The level of autophagy changes during the course of NAFLD, and the activation of hepatocyte autophagy might represent a method of treating NAFLD.